A Case Study of Productive Disciplinary Engagement in Engineering - Cogger, Steven D. (Tufts Archival Research Center, 2019)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Education.; This paper is a case study of the work done by a student in my Computer Aided Design(CAD) class. I have performed a detailed analysis of a self-selected design project where the student completes a rendering of her personal guitar. The discussion includes a focused analysis of her efforts to redesign the tuning keys, a part of the guitar assembly that the student commented on during our post-class interview. The work will show evidence of productive disciplinary engagement in engineering using the time stamps and description of the design activity generated by the CAD software as markers. The analysis provides details of the time on task indicating student engagement and evidence of the skills, knowledge, and dispositions that have been noted in the engineering education literature. The paper concludes with my thoughts the student’s work and the possibility of using the built in features of a software product to understand student thinking in engineering, to evaluate their engagement in a task, and to provide an alternative means of assessment.